2015
DOI: 10.13181/mji.v24i4.1181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripapillary retinal nerve fiber layer thickness in chronic glaucoma and non-glaucoma patients after phacoemulsification cataract surgery

Abstract: ABSTRAK ABSTRACTBackground: Phacoemulsification is a common cataract operation nowadays. During phacoemulsification, variation in intraocular pressure (IOP) may occur, which might change the retinal nerve fiber layer (RNFL) thickness. This study was aimed to evaluate the change in peripapillary RNFL thickness and mean deviation (MD) of visual field after phacoemulsification in chronic primary glaucoma and nonglaucoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The authors reported that there was increase in RNFL thickness in both the groups. 5 However, the mean change was significantly higher in glaucomatous eyes (p-value<0.001) as compared to non-glaucomatous eyes. The results were consistent with our study but their sample size was only 26 patients.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…The authors reported that there was increase in RNFL thickness in both the groups. 5 However, the mean change was significantly higher in glaucomatous eyes (p-value<0.001) as compared to non-glaucomatous eyes. The results were consistent with our study but their sample size was only 26 patients.…”
Section: Discussionmentioning
confidence: 81%
“…The sample size of 40 in each group was calculated by keeping the power of study equal to 80% and level of significance equal to 5%. 5 Patients were selected by non-probability, purposive sampling. Approval for the study was sought from the Institutional Review Board of hospital (Reference No: 00-209-20; dated 16 November 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations